BASIACUONG: ORAL TRADITION IN KAMPAR MALAY CEREMONIAL PROCESSIONS: A Living Hadith Study (TAJDID: Jurnal Ilmu Ushuluddin, 2024)
For Muslims, hadith is something very important because it contains various traditions and habits that developed during the time of the Prophet (PBUH). Indonesia is known for its various traditions and cultures in various regions where these traditions and cultures are integrated with the social life of the community. One of them is the oral tradition of Basiacuong found in the Malay community in Kampar Regency which has been applied for generations where previously it had been carried out by Kampar community leaders. This research is a field research, by tracing directly to the field of objects in the field to dig up information and obtain various data that appear in the field, by observing social phenomena that exist in the community when the tradition is carried out. The location of this research is Koto Perencaran Village, Kampar Regency, because the community in the village still maintains the oral tradition of Basiacuong and applies it in various traditional ceremonies such as marriage, circumcision, akikah, inauguration of traditional heads and so on. Data collection techniques include observation, interviews, and documentation. The results of this study conclude that the Basiacuong tradition found in the Malay community in Koto Perambahan Village, Kampar Regency is the implementation and interaction of living hadith, because the tradition contains good messages and advice, even though the tradition is carried out in traditional ceremonies.